Telescoping Implant Protheses With Galvano Mesostructures - Bratu Emanuel; Bratu Dorin; Borsanu Ioan (Romanian Society of Oral Rehabilitation, 2010)
This article will describe the technique for the fabrication of the telescoping implant prostheses with a very precise fit, achieved by luting intraorally the galvano mesostructures. The main result is the strain reduction, similar to the cemented fixed prostheses (12, 21). By the use of galvano-telescopic copings, the advantages of retrievability can be combined with the improved fit of a cemented superstructure. The telescopic system permits simple retrievability for peri-implant hygiene, and repair procedures, if necessary. The precision of implant superstructures is determined by the entire clinical and laboratory fabrication process. Errors may occur during the impression making, fabrication of the definitive cast, casting of the framework and ceramic veneering (14). Also, after extended edentulous periods, the replacement of hard and soft tissues is often necessary for esthetic or phonetic reasons. To compensate for the resorptive processes of the maxilla, a buccal flange may be required for adequate support of the lips and the facial profile. In these situations, a removable prosthesis may be given preference over a cemented fixed prosthesis or a screw retained prothesis.